2005
DOI: 10.1074/jbc.m413930200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Stat3 Sequence-specific DNA Binding and Transcription by p300/CREB-binding Protein-mediated Acetylation

Abstract: Signal transducers and activators of transcription (Stat) belong to a family of latent cytoplasmic factors that can be activated by tyrosine phosphorylation by members of the Jak tyrosine kinase family in response to a variety of cytokines and growth factors. Activated Stats form dimers and translocate into nucleus to induce expression of critical genes essential for normal cellular events. Here we report for the first time that Stat3 can be modified by acetylation both in vivo and in vitro. A major site of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
202
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(213 citation statements)
references
References 36 publications
(36 reference statements)
10
202
0
1
Order By: Relevance
“…The major STAT3 acetylation site that enhances its DNA binding activity and transactivation activity is located at its C-terminal position lysine 685 [31] . The present study demonstrated a novel mechanism of fibrogenesis mediated by STAT3 acetylation that had not been previously reported in the kidney.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The major STAT3 acetylation site that enhances its DNA binding activity and transactivation activity is located at its C-terminal position lysine 685 [31] . The present study demonstrated a novel mechanism of fibrogenesis mediated by STAT3 acetylation that had not been previously reported in the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…Although the classical view of STAT3 activation focuses on the phosphorylation on tyrosine 705 (Tyr705) and serine 727 (ser727) [30] , recent studies have shown that acetylation on lysine 685 (Lys685) of STAT3 also plays a role in transactivation of target genes [31,32] . The reversible acetylation of STAT3 is regulated by the CREB-binding protein/p300 family of histone acetyltransferases and histone deacetylases (HDACs) [31,33] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crif1 is an essential and specific transcriptional coactivator of STAT3 signalling In Crif1-null MEFs, the receptor-proximal events, tyrosine phosphorylation and dimerization of STAT3 and its nuclear translocation, occurred properly, whereas the DNA binding and transcriptional activities of STAT3 were abolished, suggesting that Crif1 might be involved in the transcription mediated by STAT3. STAT3 requires several transcriptional cofactors for the proper expression of target genes (Giraud et al, 2002;Wang et al, 2005). Histone-modifying cofactors (CBP/p300 and NcoA/SRC1a) potentiate the STAT3-mediated transcription by linking STAT3 to the basal transcriptional machinery, and directly acetylate STAT3 to enhance the sequence-specific DNA binding ability (Giraud et al, 2002;Wang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This confers either potentiation of transcriptional activity or destabilization of the enhanceosome and termination of the transcriptional response 22 . In the case of the transcription factor signal transducer and activator of transcription 3 (STAT3), which is activated by cytokine signalling, cytosolic acetylation triggers STAT3 dimerization and subsequent nuclear translocation 23,24 . Acetylation of hypoxia-inducible factor 1 (HIF1) by the ARD1 HAT apparently leads to increased association with the von Hippel-Lindau (VHL) ubiquitylation complex and proteasome-mediated degradation, which has a regulatory role in the cellular response to changes in oxygen availability and angiogenesis 25,26 .…”
mentioning
confidence: 99%